A review on criteria and decision-making techniques in solving landfill site selection problems - Mat, Nur Azriati; Benjamin, Aida Mauziah; Abdul Rahman, Syariza (Penerbit Akademia Baru, 2017)
The selection of landfill, which happens to be an environmental issue, has attracted the attention of many researchers from the fields of waste management and environmental sciences worldwide. Hence, in the attempt to overcome this problem, some decision-making techniques, including Geographic Information Systems (GIS) and Multi-Criteria Decision Analysis (MCDA), have been widely utilized in prior studies, where multiple criteria, particularly in site selection process, have been employed. With that, this article identifies the selection criteria for landfill selection and presents a review concerning decision-making techniques that have been used in past studies for two important phases involved during the process of site selection, namely, (1) preliminary site screening, and (2) assessment of site suitability. As such, some 82 articles chosen from 34 peer-reviewed journals had been investigated in detail. The results showed that 42.68% of the selected articles integrated GIS and MCDA techniques to solve the problem of landfill site selection, and this is followed by integrating GIS and fuzzy MCDA technique (18.29%). Both these techniques are indeed powerful tools that can guide decision-makers to solve problems in making decisions on the basis of various criteria under certainty and uncertainty results, mainly involving environmental issues.